'You can lead a horse to water, but you can't make it drink': the EU's and Russia's intersecting conditionalities and domestic responses in Georgia and Moldova. Issue 4 (8th August 2018) - Delcour, Laure
ABSTRACT: This article seeks to explore the conditions under which the EU's and Russia's policies actually compete in Georgia and Moldova and, the degree to which they shape domestic responses to external influences. In the face of competition for influence over the 'contested neighbourhood', one would expect EU-Russia rivalry to substantially shape domestic developments in the region. However, the article argues that Russia's and the EU's macro-level policies intersect (rather than compete) with each other and thereby create loopholes for domestic actors to pursue their own objectives. The article shows that neither the EU nor (perhaps even less so) Russia is able to substantially influence domestic developments when local actors resist change. This calls for nuancing the role played by the EU and Russia in their contested neighbourhood.